Protected areas and freshwater biodiversity: a novel systematic review distils eight lessons for effective conservation. Issue 1 (2nd December 2019) - Acreman, Michael; Hughes, Kathy A.; Arthington, Angela H.; Tickner, David; Dueñas, Manuel‐Angel
Abstract: Protected areas are a global cornerstone of biodiversity conservation and restoration. Yet freshwater biodiversity is continuing to decline rapidly. To date there has been no formal review of the effectiveness of protected areas for conserving or restoring biodiversity in rivers, lakes, and wetlands. We present the first assessment using a systematic review of the published scientific evidence of the effectiveness of freshwater protected areas. Systematic searches returned 2, 586 separate publications, of which 44 provided quantitative evidence comprising 75 case studies. Of these, 38 reported positive, 25 neutral, and 12 negative outcomes for freshwater biodiversity conservation. Analysis revealed variable relationships between conservation effectiveness and factors such as taxa assessed, protected area size and characteristics, International Union for Conservation of Nature (IUCN) protected area category, and ecoregion. Lack of effectiveness was attributed to many anthropogenic factors, including fishing (often with a lack of law enforcement), water management (abstraction, dams, and flow regulation), habitat degradation, and invasive non‐native species. Drawing on the review and wider literature we distil eight lessons to enhance the effectiveness of protected areas for freshwater biodiversity conservation. We urge policymakers, protected area managers, and those who fund them to invest in well‐designed research and monitoring programs and publication of evidence of protected area effectiveness.